Challenges of the Fourth Industrial Revolution (4IR), transformation of modern armed forces and the ethical dilemma of robotic automation - Miloradović, Nenad M.; Vukadinović, Goran M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The first industrial revolution used the power of steam and water for the mechanization of manufacturing. The second one used electricity for mass production. The third one used electronics and information technologies for the automation of production, while the fourth industrial revolution aims to enable erasing of the boundaries between the physical, digital and biological spheres in order to reach smart automation and increase the interconnection of system elements. Thus, previous industrial revolutions changed the way we work, the next one is changing the way we think. Our generation is privileged of being a contemporary of tectonic technological changes, a witness to changes that fundamentally convert production processes and relations in production, but also a witness to the changes that those products bring to the functioning of the mankind, from individuals to state organizations, including the military as well. The main goal of this paper is to indicate to the wider military academic community the need for coordination and interdependent development of combat systems, doctrine and structure of defence organizations.Methods: This paper will use general scientific methods that are used, or can be used, to acquire scientific knowledge in all scientific fields and disciplines. We highlight the hypothetical-deductive method, the analytical-deductive method and the comparative method.Results: (Increased) Еquipping with weapons and military equipment generated from the current technological revolution requires radical changes in the defence area, both in the combat component, i.e. changes of basic combat units that should optimally use these weapons (their doctrines, tactics, organization, training, etc.) as well as the administrative-bureaucratic component of the national defence system that deals with the procedures of weapons development, production and procurement, which should follow the fastest pace of innovation ever in the commercial industry area. Conclusion: The authors would like to point out the interdependence between the emerging challenges of the 4IR and the directions of transformation of modern armed forces.
Keywords: industrial revolution; organization; transformation; war; unmanned/robotized platforms